Symmetry and Convergence in Monetary Unions - Nauro F. Campos; Corrado Macchiarelli (London School of Economics and Political Science (LSE), European Institute, 2018)
This paper has three main objectives, namely to (a) propose a new framework that can support placing countries along a core-periphery continuum (beyond the more common binary treatment as either core or periphery), (b) to construct a continuous dynamic theory-based measure (the first, to the best of our knowledge) illustrating the use of this framework for a set of European countries using yearly data from 1960 to 2015, and (c) provide a first preliminary assessment, based on endogenous Optimal Currency Area (OCA) theory, of the main potential explanatory factors of the dynamics of this measure over time and across countries. Our main finding is that this new measure allows us to identify sets of countries on the basis of not only its level but also in terms of its dynamic behaviour. Using the Phillips-Sul procedure, we show the emergence a newer set of core countries (composed by Austria, Belgium, Germany, France, Italy and Netherlands), a mixed set of countries (namely Denmark, Sweden, Greece, Spain and the UK), and a set of deep-rooted periphery countries (Finland, Ireland, Norway, Portugal, and Switzerland). There are valuable lessons from the dynamics of this measure. It increases for core countries (which confirms endogenous OCA predictions), remains worrisomely constant for a periphery, and varies substantially for the intermediate set of countries. Spain (Sweden and Greece) becomes consistently more (less) core over time, Denmark's remains constant and the UK moves in and out of the core over time. Our panel estimates on a specification suggested by endogenous OCA theory imply that euro membership and more flexible product market regulations (or trade openness) make countries more likely to be in the core.
Keywords: E3; F4; 330; Symmetry; Convergence; Euro; EMU; European Union; Core-Periphery; SVAR